Forensic Examination of Electronic Documents (Law, State and Telecommunications Review, 2022)
[Purpose] The purpose of the study is to reveal the concept and essence of forensic prevention of crimes of forgery of electronic documents, to identify problems in the use of information to establish a system of countering crime and document management.[Methodology] The following approaches were used in the work: system-structural, dialectical, empirical. Forgery of electronic documents and their use is investigated not only within the framework of a single criminal case but also by a set of crimes committed depending on the mechanism that is the main one in the structure of criminal technologies.[Findings] Lack of skills and knowledge about the latest forms of documents, methods of their forgery and use in the field of forensic investigations determine the reasons for the development of this condition. The analysis of investigative and judicial practice shows that cases of forgery of electronic documents are moved to separate proceedings due to the inability to fix the person who committed the crime. In some cases, court procedures are returned for additional investigation, since investigators cannot establish mechanisms for falsification tools and bring appropriate charges.[Practical Implications] The practical significance lies in the formation of proposals for improving or making changes to the legislation, effectively improving the activities of law enforcement agencies involved in countering or combating the forgery of documents.